Using Knowledge Management System: A Taxonomy of SME Strategies - Setiyani, Lila (International Journal of Psychosocial Rehabilitation, 2020)
Research on the implementation of knowledge management systems (KMS) in an organization has been written in many scientific articles. This topic has been widely discussed since experts recognize that knowledge is a resource that can provide a competitive advantage for organizations. One interesting scientific article compiled by Roberto Cerchione and Emilio Esposito that identifies in full the taxonomy of KMS used by SME, because the use of KMS can create new opportunities for SME that cause lower- cost weight, more user-friendly and more effective. The identification results in the article clearly help SME to realize their position regarding the diffusion level and the intensity of KMS usage. Unfortunately, in this article, Roberto Cerchione and Emilio Esposito are not sufficiently clear in their method of measuring the intensity of the use of KMS (KM-Tools and KM-Practice) so that readers find it difficult to interpret the main point of the article.